Augmented Bridges: Investigating the potential of augmented reality for the design of configurable bridges. (December 2022) - Symeonidou, Ioanna; Weissenböck, Renate; Efstathiadis, Alexandros
The paper expands on the potential of using Augmented Reality (AR) for the design and customization of bridges. Following a literature review on the use of AR in architectural design, and in particular in design education, the authors discuss educational experiences gained in two digital design studios. These two courses were taught remotely at the University of Thessaly and the Frankfurt University of Applied Sciences and cross-informed each other. The teaching experiences of the authors were evaluated and subsequently used to develop the curriculum of "Augmented Bridges", an experimental AR design studio. The aim of the paper is to present current research in AR and the interactive design process of site-specific bridges, using digital and augmented media. The studio results offered valuable insight into the educational and creative value of AR technologies in architecture.